The Characterization Of The Main Characters in Janet Evanovich and Phoef Sutton’s “Curious Minds” (2016) - Wiryaswari, Nyoman Trisa Harum (Jurnal Penelitian Mahasiswa Indonesia, 2024)
Character is the most important element in a fiction story. Without characters, fiction would not exist. That’s why characters can be said to be the soul in a work of fiction. Characters who will bring the storyline to flow as it should. This study aimed to analyze the characteristics of the main character in Janet Evanovich and Phoef Sutton’s Curious Minds (2016). The author used descriptive qualitative methods in analyzing this research. The method of data collection is carried out by reading the related novel repeatedly and noting things needed for character analysis and segmentation technique according to Bordwell and Thompson. It was revealed that Emerson Knight with his brilliant, brave, introverted, out-of-the-box, eccentric, curious, and rich character traits is the key to the storyline until it finds its climax. Likewise with Riley moon. With her attractiveness, loyalty, smartness, and curiosity, she can be the best partner for Emerson in carrying out every plan. The extreme curiosity possessed by the two main characters has made the story very enjoyable. Curiosity led them to become an invincible duo and be the main key to which conflicts can be overcome even though they pass through various obstacles.